Interactive Effects of Fit Mean, Fit Dispersion, and Team-Member Exchange on Team Performance - Seong, Jee Young; Zhang, Linyuan; Hong, Doo-Seung; Yoon, Hye Jung (Journal of Ecohumanism, 2025)
This paper posits that person-group (PG) fit can be conceptualized into two distinctive subdimensions: PG fit mean and PG fit dispersion. Specifically, this study investigates how person-group (PG) fit mean, PG fit dispersion, and team-member exchange interact conceptually to influence team performance, examining the interactive effects of fit perceptions and exchange behaviors within teams at the group level in predicting team performance. The results based on a survey with full-time employees in Korea showed that the three-way interaction between PG fit, its dispersion, and team-member exchange predicts team performance. These findings highlight the importance of considering both contextual and relational factors when designing organizational strategies to enhance team effectiveness and sustainability.